7. Leukocyte Profile and Bone Fracture Recovery post Scaffold Biphasic Calcium Phosphate/Alginate implantation in Sheep - Gunanti Gunanti; Ki Agus Dahlan; Afiqah Binti Abd Latif; Liza Oktafani; Selma Laily Nur Afifa; Shayrilia Ivanovanny Angesti; Rr Soesatyoratih; Sus Derthi Widyari; Erwin Erwin (Jurnal Medika Veterinaria, 2020)
The purpose of this study is to evaluate the leukocyte profile and bone fracture recovery post scaffold biphasic calcium phosphate/alginate implantation in the sheep’s os tibia. Three sheeps involved in this study and defect is made on each left and right os tiba. Left os tibia as a control while scaffold biphasic calcium phosphate/alginate is implanted on the right os tibia. Blood is collected before and after implantation to be evaluated, while the radigoraph is used to evaluate the bone fracture recovery post biphasic calcium phosphate/alginate implantation. The result shows that scaffold biphasic calcium phosphate/alginate has no significant effect to the leukocytes profile and shows a good result on affecting the recovery process of bone fracture, although it stil not able to increase the recovery periods.